To Develop the Laws for the Benefit of Our Cities - Zykov, Sergey (project baikal, 2017)
The article indicates the necessity for a fundamental reform of the Town Planning Code. It involves the laws on architectural activity, architectural copyright, the state procurement and other regulatory acts, which should be thoroughly systematized.